Acculturation of Javanese And Malay Islam in Wedding Tradition of Javanese Ethnic Community at Selangor, Malaysia - Abid Rohmanu (Institut Agama Islam Negeri Madura, 2016)
This study is to see the level of acculturation of Javanese and Malay Islams in Javanese community wedding at Selangor Malaysia. According to the theory of culture, each culture has a uniqueness, as a individual uniqueness. The unique culture of Javanese ethnic wedding in Selangor is believed to be a process of negotiation between Malay and Javanese culture.. Acculturation theory is used in this research to explain and understand the reality of that culture. The study concluded that ethnic wedding traditions of Javanese Islam in Selangor pointed to the high level of acculturation. The acculturation leads to a “substitution” and “syncretism”. The substitution refers to the meaning that the Javanese tradition for the most replaced with new cultures (Malay). Acculturation can also be said as a cultural syncretism, the mixing of these two cultures into a new culture that are distinctive.Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i1.1008